Progestin‐primed ovarian stimulation protocol with or without letrozole for patients with normal ovarian reserve: a retrospective cohort study. (18th November 2021) - Jiang, Xing; Jiang, Shengfang; Diao, Honglu; Deng, Kai; Zhang, Changjun
Abstract: What is known and Objective: To compare the characteristics and efficacy of progestin‐primed ovarian stimulation (PPOS) protocol plus letrozole versus PPOS protocol alone for patients with normal ovarian function who received in vitro fertilization/intracytoplasmic sperm injection‐embryo transfer (IVF/ICSI‐ET) assisted pregnancy treatment. Methods: From 1 October 2017 to 1 October 2019, 576 patients who underwent IVF/ICSI cycles received PPOS protocol with or without letrozole in the Center of Reproductive Medicine, Renmin Hospital of Shiyan City were included in this retrospective cohort study. The PPOS group included 249 patients who received PPOS protocol alone, and the combined treatment group included 327 patients who received PPOS protocol plus letrozole. The general data and laboratory indicators were detected and used as baseline data. In addition, evaluation of related indicators was performed, including days of gonadotropin (Gn) duration, total amount of dose of Gn and medroxyprogesterone acetate (MPA), hormone levels on the trigger day, number of oocytes retrieved and mature eggs, fertilization rate, cleavage rate, blastocyst formation rate, high‐quality embryo rate, methods of endometrial preparation, stage of embryo transfer, endometrial thickness, the number of embryo transfer, biochemical pregnancy rate, clinical pregnancy rate, implantation rate, abortion rate, ectopic pregnancy rate and live birth rate. The risk factors affecting clinical pregnancy rate were detected by binary Logistic regression analysis. Results and discussion: In this study, we found that baseline level of Anti‐Müllerian hormone (AMH) was significantly higher in combined group compared with PPOS group ( p < 0.05). The days of Gn duration in combined group were significantly longer than that in PPOS group ( p < 0.05), and the total amount of dose of Gn and MPA in combined group was significantly less than that in PPOS group ( p < 0.05). The levels of luteinizing hormone (LH) and progesterone in combined group were significantly higher than that in PPOS group on the trigger day ( p < 0.05). The number of oocytes retrieved and mature eggs in combined group was significantly more than that in PPOS group ( p < 0.05). Meanwhile, the fertilization rate, cleavage rate and blastocyst formation rate in combined group were significantly higher than that in PPOS group ( p < 0.05). There was no significant difference in the characteristics of endometrial preparation and embryo transfer, as well as the pregnancy outcomes. The results of logistic regression analysis showed that stage ( p < 0.001) (OR = 0.281, 95% CI: 0.187, 0.422) and number ( p < 0.001) (OR = 0.333, 95% CI: 0.196, 0.567) of embryos transfer were risk factors for clinical pregnancy rate. What is new and Conclusion: Compared with PPOS protocol alone, letrozole combined with PPOS can achieve similar embryo and pregnancy outcomes while reducing the amount of Gn and MPA, which has a higher cost performance and is worth promoting. Stage and number of embryos transfer are risk factors for clinical pregnancy rate.